Growing public spaces in the city: Community gardening and the making of new urban environments of publicness. (November 2021) - Milbourne, Paul
The demise of public space in cities across the Global North has received considerable scrutiny from urban scholars in recent years, with accounts of the loss, privatisation and increased regulation of public space prevalent within the academic literature. This paper seeks to complicate these dominant narratives of public space transformation by exploring the complexities of existing public spaces and the emergence of new spaces of publicness in the city. It uses a case study of community gardening in mundane and everyday neighbourhood spaces to provide a more nuanced and progressive reading of the relations between publicness and space in the city. Drawing on empirical materials from recent research on community gardening projects in 15 cities in Australia, Canada, the UK and the USA, the paper highlights how community gardening is creating new environments of publicness across public, private and in-between spaces that complicate both the end of public space discourse and conventional understandings of public space within urban studies.